Analysis of the Narrative of Depression Content on the Instagram Account @Insightme.Id - Agraha, Alice; Isnaini, Muhamad; Girsang , Lasmery Rosentauly Maissalinya (Asian Journal of Social and Humanities, 2025)
Instagram is a social media that plays a role in providing the latest information through content. Through content about depression that is uploaded on the Instagram account @insightme.id periodically, it can help to provide psychoeducation and understanding related to the importance of mental health awareness, especially regarding depressive disorders. The purpose of this study was to conduct a narrative analysis on content that discusses depressive disorders on the Instagram account @insightme.id. This study is a research with a descriptive qualitative approach using a content analysis method that focuses only on depressive content on the Instagram account @insightme.id with a period of time that has been determined by the researcher. Based on the results of the research, regarding the narrative of depression content on the Instagram account @insightme.id it was found that overall the depression content uploaded has used an effective and appropriate narrative to provide information and play a role in building awareness about depression disorder, especially to the followers of the Instagram account @insightme.id by creating content that has a narrative of empathy and a sense of involvement and support for @insightme Instagram followers. id.